Female income and late marriage in Singapore. - Mah, Yeok Tho. (2008)
The main objective of this study is to provide a better understanding of the current trend in Singapore marriage rate from the perspective of opportunity costs. This study is divided into two main sections. In the first section, we will examine whether the opportunity costs of getting married is increasing among females in Singapore by using some indicators which include female labour force participation rate, income, education level and income ratio between males and females. In the second section of this study, we will discuss policies that the Singapore government has introduced over the years in order to decrease the opportunity costs of marriage among women.